PELAKSANAAN PROMOSI TAMAN WISATA SURYA FAM’S KECAMATAN KUANTAN TENGAH PROVINSI RIAU - Puspanegara, Enrica Seavina; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the implementation of Surya Fam's Tourism Park promotion in Kuantan Tengah District, Kuantan Singingi Regency, Riau Province. The promotional strategies implemented include personal selling, mass selling, sales promotion, public relations, and direct marketing. The research method used is descriptive qualitative, with data collected through interviews, observations, and documentation. The results of the study indicate that promotion through social media, such as TikTok, Facebook, and Instagram, plays a significant role in increasing the popularity of the tourism park. Personal selling strategies involving direct communication and creativity also succeeded in attracting visitors. In addition, community-based promotions, such as providing discounts for groups, also support the increase in the number of visits. However, this study also identified obstacles such as limited human resources and lack of technological knowledge to support digital promotion. The study concluded that planned and integrated promotions can increase the attractiveness of Surya Fam's Tourism Park as a leading family tourism destination. Recommendations provided include training for managers, strengthening digital promotions, and collaborating with local governments to expand the reach of promotions. This strategy is expected to encourage the development of tourism parks in a sustainable manner. Keywords: Surya Fam's Tourism Park, Promotion, Family Tourism Destination, Tourism Development, Promotion Constraints.